2014
DOI: 10.1111/flan.12121
|View full text |Cite
|
Sign up to set email alerts
|

Peer Mentoring Second Language Teachers: A Mutually Beneficial Experience?

Abstract: Studies have shown that there are not enough qualified foreign language and English as a second language teachers in this country. To increase the number of new second language teachers who remain in the profession, and to promote their use of best teaching practices, the ACTFL has identified mentoring as a national research priority. The importance of mentoring is further reflected in the new national standards established by the Council for Accreditation of Educator Preparation (CAEP) for teacher education p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…Considering the evidence which shows that programs that are specific to the needs of foreign language teachers are more effective than generic programs (Brown 2001;Ewart 2009;Kissau & King 2015;Wilkerson 2000), more effort is needed to develop and implement programs that are specifically designed for foreign language teachers.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the evidence which shows that programs that are specific to the needs of foreign language teachers are more effective than generic programs (Brown 2001;Ewart 2009;Kissau & King 2015;Wilkerson 2000), more effort is needed to develop and implement programs that are specifically designed for foreign language teachers.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its uniqueness in the target of feedback, this study seems meaningful in that it paid attention to the mutual benefit of peer feedback both for the givers and receivers. Kissau and King"s (2015) study also deserves attention in that it is one of the few studies on peer feedback ("peer mentoring" in their terms) that involved L2 teacher-trainees, given that, as already mentioned, studies on peer feedback have largely been situated in writing classrooms. After one semester of one-to-one matched mentoring project where a mentor observed the classes the mentees taught and had conferences with questions and answers about those classes, the researchers found that both parties benefitted from such experience especially when they greatly shared commonalities in areas such as age, previous experience, and content domain expertise, and when the manner of co-work was supportive rather than judgmental.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
“…Additionally, there is a need for research on ESL mentoring to provide a better understanding on the effective roles of ESL mentors (Brown 2001, Kissau & King 2014. The present study postulated several effective roles of ESL mentors which include as a speaking partner and as a source of reference.…”
Section: Mentors' Rolesmentioning
confidence: 78%
“…There are vast literature on the benefits of mentoring particularly for the novice teachers. However, there is scarce literature that examines closely the novice teachers' learning experience that takes place during mentoring (Kissau & King 2014, Delaney 2012, Kardos & Johnson 2007, Mann & Tang 2012. Hence, this study seeks to fill in the gap in the existing literature by exploring the learning experience of novice ESL teachers who participated in the Native Speaker Programme.…”
Section: Introductionmentioning
confidence: 99%